2015
DOI: 10.1002/cne.23936
|View full text |Cite
|
Sign up to set email alerts
|

Mapping chromatic pathways in the Drosophila visual system

Abstract: In Drosophila, color vision and wavelength-selective behaviors are mediated by the compound eye's narrow-spectrum photoreceptors, R7 and R8, and their downstream neurons, Tm5a/b/c and Tm20, in the second optic neuropil, or medulla. These chromatic Tm neurons project axons to a deeper optic neuropil, the lobula, which in insects has been implicated in processing and relaying color information to the central brain. The synaptic targets of the chromatic Tm neurons in the lobula are not known, however. Using a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…ML1 is a new, major target of R8, a cell type that connects the medulla to the lobula via a previously unknown, non-columnar pathway, and the central brain (Figure 4D, Figure 11Aii). Previous studies have identified an important role for Tm5a/b/c and Tm20 cell types for chromatic processing in the lobula (Lin et al 2016;Gao et al 2008), and we have confirmed that these cell types are targets of R7-8. Whether these Tm neurons and ML1 cells have common targets in the lobula, feed into shared central pathways or contribute to separate channels remain open questions; the lobula arbors of the Tm and ML1 cells are mostly in different layers arguing against direct synaptic interactions between the cells.…”
Section: Inner Photoreceptor Connections Outside the Medulla Neuropilsupporting
confidence: 87%
“…ML1 is a new, major target of R8, a cell type that connects the medulla to the lobula via a previously unknown, non-columnar pathway, and the central brain (Figure 4D, Figure 11Aii). Previous studies have identified an important role for Tm5a/b/c and Tm20 cell types for chromatic processing in the lobula (Lin et al 2016;Gao et al 2008), and we have confirmed that these cell types are targets of R7-8. Whether these Tm neurons and ML1 cells have common targets in the lobula, feed into shared central pathways or contribute to separate channels remain open questions; the lobula arbors of the Tm and ML1 cells are mostly in different layers arguing against direct synaptic interactions between the cells.…”
Section: Inner Photoreceptor Connections Outside the Medulla Neuropilsupporting
confidence: 87%
“…29,[34][35][36]38,[43][44][45][46] To understand how each type of output synapse from KCs might be influenced by sleep loss, we used GFP reconstitution across synaptic partners (GRASP) 80,81 to observe synaptic contacts between KCs and their various synaptic targets in rested and sleep-deprived flies (sleep traces shown in Figures S5). GRASP has previously been used to identify patterns of synaptic contacts in worms, [82][83][84] flies, 81,[85][86][87][88] and mice 89,90 using light microscopy. Here, we expressed an activity-dependent GRASP reporter to label recently active contacts in which KCs release neurotransmitter onto a synaptic partner of interest.…”
Section: Divergent Consequences Of Sleep Loss On Kc Output Synapse Classesmentioning
confidence: 99%